Analisis Kondisi Fisik pada Atlet Putra Floorball Surabaya - Pandang Sauma RS; Made Pramono; Purbodjati; Muhammad Dzul Fikri (Jurusan Pendidikan Kesehatan dan Rekreasi, 2021)
Background: This study aims to measure the level of speed, agility, and aerobic endurance of floorball in Surabaya. Methods: This type of quantitative descriptive research was used, with data collection techniques in the form of a 30-meter running speed test, flexibility test, aerobic endurance test which later calculated the mean, percentage of the tests that had been carried out by athletes. The sample was determined as many as 15 male athletes with the research time on March 30-31 2022 at Gor Bima, State University of Surabaya. Conclusions: The conclusion that can be drawn from the tests conducted on 15 floorball is that an average score of 84.79% was found in the overall test athletes, namely 30 meter running, bent knee sit-ups, push ups, and MFT.